Stem-cutting dipping in insecticides and biopesticide application for the control of Bemisia tabaci whitefly in cassava - Amour, Massoud; Issa, Khamis A.; Wosula, Everlyne N.; Ndalahwa, Mathias; Stephano, Flora; Chandler, David; Ndyetabula, Innocent; Legg, James P. (Frontiers in Agronomy, 2025)
IntroductionThe whitefly, Bemisia tabaci, is a serious pest of cassava that causes yield loss through physical damage and vectoring of viruses that cause devastating cassava mosaic (CMD) and cassava brown streak (CBSD) diseases. The objective of this study was to evaluate the efficacy of commercially available entomopathogenic fungi biopesticides (EPFs) and cutting dipping in insecticides alone and in combination with spraying EPFs against cassava B. tabaci.MethodsLaboratory experiments were conducted to test three commercial EPFs against cassava whitefly at IITA Tanzania. Data were recorded for nymph mortality. Field experiments were conducted at three Tanzania Agricultural Research Institute (TARI) stations (Chambezi, Mkuranga, and Ukiruguru) to evaluate the efficacy of two EPFs, and the efficacy of cutting dipping in insecticides combined with spraying EPF against B. tabaci during the period of December 2021 to August 2023. The experimental design for field experiments was a randomized complete block design with four replicates. The data recorded for field experiments were on whitefly and nymph numbers, CMD and CBSD incidence and severity, and root yield.Results and discussionMortality levels caused by EPFs under laboratory conditions were 35%–86% at 14 days after application. In field experiments, EPFs reduced the proportion of healthy nymphs by 64%–75% compared with the control, with no effect on adult whitefly numbers, CBSD, and root yield. For cutting dips in insecticides at Chambezi, MandiPlus, the most effective treatment, reduced adult whiteflies by 85% and nymphs by 88%, CMD incidence by 59%, and CBSD by 46% and increased stem number by 119% and root yield by 50%.ConclusionThese findings confirm that the application of MandiPlus through cutting dips is effective at reducing whitefly populations on cassava in Tanzania, reducing virus incidence and increasing yield. Application of entomopathogenic fungi under field conditions for control of cassava whitefly does not confer any significant benefits in terms of disease reduction and yield gain. Cutting dipping in insecticides is recommended for adoption as a component in IPM strategy for managing whiteflies and the viruses that they transmit.